Morphological and quality characteristics of genus of Canarium L.: a review - A Rashid, N. A. H.; Shamsudin, R.; Arifin, S. H.; Z Abdullah, W. N. Z. (Institute of Physics Publishing, 2021)
The genus Canarium L. comprises 75 species of aromatic trees which are found in the rainforests of tropical Asia, Africa and the Pacific. A literature review was conducted through published works to gather information on nutritional and ethnic values, colour, shape, fatty acid and also antioxidant activities of Canarium sp. The phytoconstituents which are present in most Canarium L. genus especially its fruit are mainly phenolic and fatty acid which are responsible for the actions. This novel compound serves as a contributor to the antioxidant capacity of Canarium fruit and thus, the genus can be recommended as a major source of natural antioxidants. However, this genus still can be categorised as underutilised fruit and little study is paid on its collection and comparison amongst species of Canarium L. species. Thus, the present review summarizes some such attributes of the Canarium L. genus.